Bag masken atter en maske: Om kunst, okkultur og det politisk mærkelige - Opstrup, Kasper (K&K - Kultur og Klasse, 2023)
This article investigates concatenations of art, activism and occultism in contemporary art and politics while it, simultaneously, develops a notion of the ‘political weird’. Beginning with the Gruppo di Nun’s manifesto for a revolutionary demonology, the article traces the interconnectedness between art, politics, and the occult in a historical perspective, using the tactical media scenes from the 90s, with a particular focus on the Luther Blissett project, as a primary point of comparison to the Nun group. This leads to a reflection on the use of myth functions and hyperstitions as ways of destabilizing truth to make art happen and move it from the fictional to the factual, as well as to a discussion of what happens when political terms are being swapped with occult terms as an act of activism. The article argues that this can be seen as attempts on world building that challenge consensual reality in order to construct new commons, new subjectivities, and new outsides. The political weird insists that there is an outside and appears when this outside breaks into the present order. It is constituted by irruptions of the irrational and a presence of something that does not belong. Speculating about this outside as a place where barbarians roam, the article, in a final analysis, looks at the intellectual barbarianism of the Kindred of the Kibbo Kift, a youth movement possessed by more than a touch of surrealism which grew out of the British woodcraft movement in the 1920s. The Kift wanted to invoke another future populated by new barbarians through the realization of art and fictional ideas from not only Rosicrucianism but also authors like James Fenimore Cooper and H. G. Wells. This, they hoped, would bring about a new era of world peace and universal brotherhood.